Relentless improvement : true stories of lean transformations - Trudell, Bill (CRC Press, 2013)
Tracing the author's decades-long continuous improvement journey, Relentless Improvement: True Stories of Lean Transformations walks readers through vivid shop floor experiences to convey a genuine feel for the environments in which Lean Six Sigma transformations occur. Recounting numerous Lean Six Sigma transformations, it illustrates the spectrum of successful operational tactics. The story starts just outside Detroit, Michigan in the 1970s when the auto industry was booming, and most people in the area worked in the car factories, or in one of the component factories that supplied the Big T.